2009
DOI: 10.1111/j.1740-0929.2009.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with conjugated linoleic acid on fatty acid composition and lipid oxidation in chicken breast meat

Abstract: We investigated the effects of dietary conjugated linoleic acid (CLA) on fatty acid composition and lipid oxidation in breast meat of broiler chickens. Broiler chickens (28-day-old females) were fed diets containing experimental oils at 20 g/kg diet for 28 days. The experimental oils consisted of either a 2:0, 1:1, or a 0:2 (wt : wt) ratio of safflower oil (high linoleic acid content) to a commercial CLA mixture. In this study, dietary CLA supplementation significantly increased the composition and content of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…The result is consistent with previous studies on the poultry animal model (Du et al 2001;Bolukbasi 2006;Kawahara et al 2009;Narciso-Gaytan et al 2011). Moreover, in a study by Wiegand et al (2002), growing-finishing barrows were fed a diet enriched with 0.75% CLA and the lipid oxidation level decrease of chops at days 1, 14, and 28 of retail storage was observed.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The result is consistent with previous studies on the poultry animal model (Du et al 2001;Bolukbasi 2006;Kawahara et al 2009;Narciso-Gaytan et al 2011). Moreover, in a study by Wiegand et al (2002), growing-finishing barrows were fed a diet enriched with 0.75% CLA and the lipid oxidation level decrease of chops at days 1, 14, and 28 of retail storage was observed.…”
Section: Discussionsupporting
confidence: 80%
“…The increase of thiobarbituric acid reactive substances (TBARS) values, the lipid peroxidation maker for the minced breast muscle was inhibited by dietary CLA (Kawahara et al 2009). TBARS values in the breast and thigh muscles of broiler chickens were significantly influenced by dietary CLA and storage time, and dietary CLA significantly decreased TBARS in breast and thigh meat after a 7-day storage at 4°C (Bolukbasi 2006).…”
mentioning
confidence: 99%
“…Conjugated structure of linoleic acid made the fatty acid less susceptible to free radical attacks (Du et al, 2000). Additionally, CLA would behave like MUFA and reduce lipid oxidation by minimizing the initiation step of lipid oxidation (Du et al, 2001;Kawahara et al, 2009). Jiang et al (2014) confirmed that dietary supplementation with 1% CLA had positive effects on meat quality, antioxidant capacity and fatty acid composition of broilers.…”
Section: Discussionsupporting
confidence: 50%
“…Dhiman et al (2005) also confirmed that CLA in milk or meat was stable compound under normal cooking and storage conditions. The CLA isomeric profile showed a clear predominance of the bioactive cis-9,trans-11 isomer in all experimental treatments (Kawahara et al, 2009). No changes were identified after beef cooking in the relative proportions of the bioactive cis-9,trans-11 isomer, likewise, trans-10,cis-12, was not influenced by heating treatments (Alfaia et al, 2010).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation